Airport Representatives’ Role in Handling Foreign Tourists: Case Study at Panorama Destination Bali - Sofyan Riyandi; Made Darmiati; Putu Ayu Aryasih (Politeknik Pariwisata Bali, 2024)
This study aims to analyze the role of Airport Representatives at Panorama Destination Bali in managing the arrival and departure processes of foreign tourists at I Gusti Ngurah Rai Airport Bali. This research uses a qualitative descriptive method, the results of direct observation in the field and the distribution of questionnaires to two different classifications of respondents. The first group of 23 staff members of Panorama Destination Bali staff while the second group consists of 8 foreign tourists who use the service. The findings of indicate that Airport Representative plays a crucial role in ensuring a positive traveler experience at the airport, starting from when tourists arrive to when tourists depart. They are not only responsible for assisting with the logistics of arrival and departure but also provide necessary information and support to tourists. The staff respondents emphasized the importance of communication skills and thorough knowledge of airport procedures, while tourists highlighted the sense of security and comfort provided by the Airport Representatives. Overall, this study confirms the important role of Airport Representatives in the tourism industry, particularly in enhancing the satisfaction of foreign tourists visiting Bali. The findings offer valuable insights for airport managers and travel agents aiming to improve their services.